Fresamento com comando numérico computadorizado em madeiras de Corymbia e de Eucalyptus: análise do consumo de energia - Silva, Elder Marcos da (2016)
Researches have been developed to determine better conditions for the mechanical processing of wood in relation to the cost and quality of the final product. Technology improvement aiming at controlling the cutting forces has become an incessant search within the industry. In addition, in Brazil, there are proposals for the better use of woods from planted forests, especially of Eucalyptus, for use on products of higher added value, such as furniture and frames. To establish the adequate feeding and cutting speed that allow the reduction of energy intake, we measured and analyzed the cutting power of Corymbia and Eucalyptus woods of different densities, during its hobbing. The woods used were Corymbia citriodora, C. maculate, Eucalyptus deglupta, E. pilularis and E. microcorys, with apparent densities of 0.425 g cm -3 and 1.085 g cm -3 , from an experimental plantation. Samples were manufactured and machined in milling machine with computerized numeric command. The millings were carried out at parallel, perpendicular and 45 o in relation to the grain. The circular milling was also performed. For the readings of the cutting power, we used the energy quality analyzer. The results showed an increase in power intake with the increase of feeding and cutting speed, as well as with the increase in density. The cut in the direction perpendicular to the fibers presented higher power intake when compared to the parallel cut. In average, we verified a decrease of 12% of active power intake when altering the cutting speed from 3.77 m s -1 to 7.54 m s -1 , with feeding speed of 1.39 m min -1 . Regardless of the analyzed species, lower feeding speeds, associated to higher cutting speeds presented lower active power intake.